INTERNAL STRESSES IN MARTENSITE FORMATION IN COPPER BASED SHAPE MEMORY ALLOYS - Adiguzel, Osman (Springer, 2010)
Shape memory alloys constitute a class of materials called smart materials which exhibit an unusual property, shape memory effect. The behaviour of these materials is evaluated by the structural changes caused by internal stresses in microscopic scale. Copper based alloys exhibit this property in beta-phase field. Shape memory alloys undergo a solid state phase transition, martensitic transition by means of lattice invariant shears and Bain distortion on cooling from high temperatures. Both distortions are caused by the internal stresses in the material. The lattice invariant distortion involves the introduction of stacking sequences on one of the close packed {110}(beta) planes of matrix called martensite basal plane. The formation and evolution of the layered structure in copper based ternary shape memory alloys consist of lattice invariant shears and shear mechanism. Shape memory elements cycle between the deformed and undeformed shapes against the temperature changes while using in the devices. These alloys can be used as actuator or sensor due to this property.
NATO Advanced Research Workshop on Advanced Materials and Technologies for Micro/Nano-Devices Sensors and Actuators -- JUN 29-JUL 02, 2009 -- St Petersburg, RUSSIA
Keywords: Martensitic transition; shape memory effect; Bain distortion; layered structures; internal stresses; shear stress; thermoelasticity; superelasticity